High-density planting system in subtropical fruit crops - Singh, V K (Indian Horticulture, 2018)
High-density planting technique is a modern method of fruit cultivation involving planting of trees densely, allowing small or dwarf trees with modified canopy for better light interception and distribution. Pests and disease control, weeds and pruning operations are mechanized. Irrigation and fertigation are automatically controlled. Such system produces precocious cropping, high and regular yield of quality fruits and low labour requirement to meet ever rising production costs. It is possible by regular training, pruning, use of bioregulators and mechanization for maintaining the size and shape of trees. These technologies need to be adopted at a larger scale and the progressive farmers should act as a training centre of modern fruit production.